Employee Performance Satisfaction, Turnover Intention as an Intervening and Perceived Organizational Support as a Moderation in PT Karya Prima Multisarana - Christina Anggraini; Rosita Bangun (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2026)
This study aims to analyze the influence of job satisfaction and the work environment on employee performance, with turnover intention as an intervening variable and perceived organizational support as a moderating variable, in PT. Karya Prima Multisarana. The research approach uses quantitative methods with surveys. The research population includes all employees of PT. Karya Prima Multisarana, with a sample of 100 respondents, was determined through saturated sampling techniques. Data were collected using a questionnaire and analyzed using the Partial Least Squares (PLS) method in SmartPLS 3. The study's results show that job satisfaction has a significant effect on employee performance and turnover intentions. The work environment does not significantly affect employee performance, but it does substantially affect turnover intention. Turnover intention has a significant impact on employee performance and serves as a mediator of the effects of job satisfaction and the work environment on employee performance. In addition, perceived organizational support has a substantial impact on employee performance. Still, it has not been shown to moderate the effects of job satisfaction and the work environment on turnover intention. This study emphasizes the importance of increasing job satisfaction and managing turnover intention in an effort to improve employee performance in a sustainable manner.